Serum Cystatin C Levels Are Associated With Obesity in Adolescents Aged 14–17 Years - Huo, Ying-Xiang; Wei, Wei; Liu, Yang; Ma, Ya-Nan; Tao, Jun-Min; Wang, Ning-Ning; Li, Xiao-Feng; Chen, Xin (Frontiers in Endocrinology, 2022)
Background: The association between serum cystatin C levels and obesity has not been fully explored in adolescents. This study aimed to explore the association between serum cystatin C levels and obesity in adolescents of different sexes. Methods: We conducted a cross-sectional study including 481 adolescents aged 14−17 years. Cystatin C level was measured by immunoassay. Health examination data, biochemical parameters, and questionnaire information were collected. The restricted cubic spline model analyzed the association between cystatin C levels and obesity in boys and girls. Results: Boys exhibited significantly higher cystatin C levels than girls, with a mean level of 0.97 ± 0.10 mg/L in boys and 0.86 ± 0.09 mg/L in girls (P < 0.001). The restricted cubic spline model suggested that low or high cystatin C levels were associated with an increased risk of obesity in boys, whereas only higher cystatin C levels were associated with an increased risk of obesity in girls. Conclusions: A U-shaped correlation was observed between serum cystatin C levels and the risk of obesity in boys. However, in girls, the risk of obesity showed a trend of initially increase and then decrease with increasing cystatin C levels. Longitudinal studies should be conducted to further investigate the diagnostic potential of cystatin C in the progression of early obesity in adolescents of different sexes.